Interaction design for dyslexic children reading application: A guideline - Aziz, Fakhrul Anuar; Husni, Husniza (2012)
This paper outlines and explains the guideline needed to design an effective interaction design (IxD) for dyslexic children’s reading application.The guideline is developed based on theories that underly dyslexia and its effects towards reading, with emphasis given to the visual related theories and phonological deficit theory and core-affect theory.The needs of a dyslexic child to read properly and correctly with understanding of the related theories inspires the development of this guideline as it is aimed to aid the process of learning to read by facilitating them with useful design.Tested on a number of dyslexic children, the design seems to reduce their memory load for this particular task and thus reduce their difficulties in reading.Hence the role of an interaction designer is needed to answer the whats and hows and to design an interactive product (in this case–reading applications) to help dyslexic children to read.